Exploring everyday relations with animal research: a sociological analysis of writing from the Mass Observation Project - McGlacken, Renelle (2021)
This thesis explores how the topic of laboratory animal research is related to in everyday life in the UK, providing a sociological analysis of practices of knowing, caring, and constructing necessary biomedical uses of animals. In doing so, it develops the few qualitative studies of societal understandings of animal research, aiming to expand analyses in this area beyond measurement of polarised and static notions of acceptance or opposition. Instead, this thesis approaches understandings of animal research as relational and positional, emerging within particular yet shared social worlds which give the issue meaning in the everyday. Such a stance goes beyond efforts to observe what people think or know about animal research which dominate previous studies in this area and, instead, opens these categories up further to explore what animal research means to individuals and why. In this way, the thesis challenges assumptions of passive absorption of information on the issue and accusations of public ignorance or misunderstanding.